2022
DOI: 10.3390/jpm12050838
|View full text |Cite
|
Sign up to set email alerts
|

Constipation Symptoms in Multiple System Atrophy Using Rome Criteria and Their Impact on Personalized Medicine

Abstract: Constipation is one of the most common non-motor symptoms in multiple system atrophy (MSA); however, it has not been evaluated according to the standard diagnostic criteria for constipation in patients with MSA. We evaluated the characteristics of constipation in patients with MSA by using Rome criteria (Rome III), which has been validated and the widely used for gastrointestinal disorders. Fifty-one patients with MSA (29 female) were enrolled in the study. Based on the Rome III criteria, constipation was diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Like PD, MSA is an α-synucleinopathy, but with the aggregate α-synuclein deposited in the glia [293]. Constipation is also common in MSA [294].…”
Section: Multisystem Atrophymentioning
confidence: 99%
“…Like PD, MSA is an α-synucleinopathy, but with the aggregate α-synuclein deposited in the glia [293]. Constipation is also common in MSA [294].…”
Section: Multisystem Atrophymentioning
confidence: 99%
“…While in MSA and PSP, NMS is still poorly investigated in clinical practice and remains undeclared. Some studies have investigated a few individual NMS in MSA ( 13 15 ), but few studies have systematically investigated NMS of MSA ( 16 , 17 ), so does the studies on PSP ( 18 20 ). Previous studies have compared individual NMS between MSA, PD, and PSP ( 21 27 ) and found that NMS may be useful in the differential diagnosis between MSA and PD/PSP.…”
Section: Introductionmentioning
confidence: 99%